2019
DOI: 10.1111/fwb.13254
|View full text |Cite
|
Sign up to set email alerts
|

Egg development and hatching success in alpine chironomids

Abstract: Climate change affects both alpine freshwater ecosystems and their benthic communities, dominated by Chironomidae (Diptera). Previous studies assigned each chironomid species a narrow thermal niche and a correspondingly high sensitivity towards global warming. Nevertheless, to date no study has examined egg development although the potential effect of changing temperatures on this initial phase of life might be crucial to existence and/or survival in harsh environments. Adaption towards low temperatures might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The averaged original dataset revealed that at the coldest treatment, Diamesinae had a lower day-degree demand (36.2 ± 7.2) than Orthocladiinae with 52.8 ± 11.8 ( Figure 3A,B). As highlighted in the original study [19], the averaged degree-day demand across chironomid species was also significantly higher with a higher breeding temperature. The lowest demand was found for Diamesinae in the coldest breeding temperature (2 • C) with on average 36.2 ± 7 degree-days, whereas the highest demand of the same subfamily was at 12 • C with 95.7 ± 18.8 degrees-day ( Figure 3B).…”
Section: Development Of Eggs and Larvae In Relation To Catchment Glacmentioning
confidence: 66%
See 4 more Smart Citations
“…The averaged original dataset revealed that at the coldest treatment, Diamesinae had a lower day-degree demand (36.2 ± 7.2) than Orthocladiinae with 52.8 ± 11.8 ( Figure 3A,B). As highlighted in the original study [19], the averaged degree-day demand across chironomid species was also significantly higher with a higher breeding temperature. The lowest demand was found for Diamesinae in the coldest breeding temperature (2 • C) with on average 36.2 ± 7 degree-days, whereas the highest demand of the same subfamily was at 12 • C with 95.7 ± 18.8 degrees-day ( Figure 3B).…”
Section: Development Of Eggs and Larvae In Relation To Catchment Glacmentioning
confidence: 66%
“…This study was built upon recent field surveys carried out on alpine streams and rivers within our long-term monitoring program. Besides presenting data on environmental conditions, as well as structural and functional characteristics (assessments in 2014), we re-analyzed some experimental raw data from already published sources (physiological data [17], isotope data [18], and experimental data [19], assessments in 2014, 2015, and 2017, respectively), where we think these new results specifically mirror functional assets in harsh environments, such as glacial rivers. We specifically aimed at defining cause-effect relationships (glacier cover vs. functions) by overlaying the invertebrate community data and environmental settings with the functional characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations